(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The study investigates B.Ed. teacher trainees' attitudes towards Continuous Internal Assessment (CIA) and the factors influencing these attitudes. Recognizing that one-time examinations can overburden learners and fail to properly assess continuous learning progress, the research emphasizes the benefits of CIA in maintaining cumulative records of progress and enhancing teaching effectiveness. Using a mixed-method research design, a sample of 600 B.Ed. teacher trainees undergoing B.Ed. courses under Manipur University during the 2023-24 academic years was selected through stratified random sampling for the quantitative phase. Based on attitude scores, 54 trainees (30 females and 24 males) scoring ≤162.00 (90th percentile) were chosen for the qualitative phase. A self made standardized questionnaire assessed attitudes towards CIA for quantitative data, while in-depth interviews gathered qualitative insights. Quantitative data were analyzed using mean, t-test, and ANOVA, and qualitative data were thematically analyzed. Results indicate that male and female trainees, as well as arts and science, and rural and urban trainees, hold similar attitudes towards CIA. However, female, rural, and private category trainees showed less favorable attitudes compared to their counterparts. Interviewees identified factors influencing their attitudes, including perceived usefulness, fairness, institutional support, motivation, past experiences, perceived control, peer influences, and cultural factors. To foster favorable attitudes towards CIA, the study recommends providing teacher trainees with adequate guidance, teaching-learning materials, and appropriate infrastructure.